Histopathological spectrum of lesions of tonsil- A 2 year experience from tertiary care hospital of Maharashtra, India - Ranjitsingh Sulhyan, Kalpana; Dattatraya Deshmukh, Bhakti; Pramod Wattamwar, Reshma (International Journal of Medical Research and Review, 2016)
Background: Palatine tonsils are paired masses of lymphoid tissue which act as immunologic barrier against the entry of pathogenic agents into the respiratory and digestive tracts. Despite their protective function, tonsils are prone to infection. Tonsillitis is a common disease especially among the children. Chronic tonsillitis is a disease with repeated attacks of acute tonsillitis or a subclinic form of a resistant or poorly treated infection. Aim: To study histopathology of various lesions of tonsil. Material and Methods: We studied histopathology of 211 cases representing surgical samples from 115 patients [Tonsillectomy- 104 patients (Unilateral-08, Bilateral-96) and tonsillar biopsy in 11 patients]. Representative bits were taken from formalin fixed tonsillectomy specimens whereas biopsies were submitted entirely. Routine hematoxylin and eosin staining was done. Results: Amongst 211 cases, histopathological examination in 190 cases showed tonsillitis. The other lesions were cartilagenous choristoma in six patients, epidermal inclusion cyst in three cases and reactive lymphoid hyperplasia in one case. One case of inflammatory myofibroblastic tumour was observed. The malignancies were observed in ten cases- squamous cell carcinoma in nine cases and Non-Hodgkin lymphoma in one case.